Ferlinghetti [videorecording (DVD)] : a rebirth of wonder - Felver, Christopher, 1946-; Ferlinghetti, Lawrence; Ginsberg, Allen, 1926-1997; Hopper, Dennis, 1936-2010; Collins, Billy; Felver, Christopher, 1946- (First Run Features, 2013)
This incisive and entertaining portrait of American poet Lawrence Ferlinghetti explores his vital role as catalyst for numerous literary careers and for the Beat movement itself. Interviews with Ferlinghetti and others reveal a rich mľange of characters and events that unfolded in postwar America. In 1953 Ferlinghetti opened City Lights Bookstore, which quickly evolved into an iconic institution symbolizing social change and literary freedom. Six decades later, it is still going.